Characterization of whole-genome autosomal differences of DNA methylation between men and women. Issue 1 (December 2015) - Singmann, Paula; Shem-Tov, Doron; Wahl, Simone; Grallert, Harald; Fiorito, Giovanni; Shin, So-Youn; Schramm, Katharina; Wolf, Petra; Kunze, Sonja; Baran, Yael; Guarrera, Simonetta; Vineis, Paolo; et al.
Abstract Background Disease risk and incidence between males and females reveal differences, and sex is an important component of any investigation of the determinants of phenotypes or disease etiology. Further striking differences between men and women are known, for instance, at the metabolic level. The extent to which men and women vary at the level of the epigenome, however, is not well documented. DNA methylation is the best known epigenetic mechanism to date. Results In order to shed light on epigenetic differences, we compared autosomal DNA methylation levels between men and women in blood in a large prospective European cohort of 1799 subjects, and replicated our findings in three independent European cohorts. We identified and validated 1184 CpG sites to be differentially methylated between men and women and observed that these CpG sites were distributed across all autosomes. We showed that some of the differentially methylated loci also exhibit differential gene expression between men and women. Finally, we found that the differentially methylated loci are enriched among imprinted genes, and that their genomic location in the genome is concentrated in CpG island shores. Conclusion Our epigenome-wide association study indicates that differences between men and women are so substantial that they should be considered in design and analyses of future studies.